Perbedaan Perkembangan Bahasa Anak Pra Sekolah yang Mengikuti dan Tidak Mengikuti PAUD - Yuliana Purnama Dewi; Artika Nurrahima (Holistic Nursing and Health Science, 2019)
Background: Delay in language development can affect subsequent development in children. Research comparing language development of pre-school age children who participated and did not participated in PAUD had never been done before. The purpose of this study was to analyze differences in language development of pre-schoolers who attended Early Childhood Education (PAUD) and did not attend Early Childhood Education (PAUD).Methods: This research was a quantitative research with comparative descriptive method. The sampling technique was proportionate random sampling and involved of 82 children in Bulusan Village, Tembalang District, Semarang City. Data analysis used Kolmogorov-Smirnov test.Results: The results showed that the language development of pre-schoolers attending the early childhood was better than the non-attending pre-schoolers with p-value from non-parametric test Kolmogorov Smirnov (0.032) <α (0.005).Conclusion: There are differences of preschool language development who attended and did not attend PAUD. Based on the results of the study, it is advisable for parents of children to provide stimulation appropriate to the stage of language development of children according to their age and to include children in PAUD.